Advancement on Digestive Tract Biomedical Stents, A Review (Journal of Fiber Bioengineering and Informatics, 2023)
Biomedical stents for the digestive tract address many of the limitations associated with traditionalsurgical treatments for gastrointestinal diseases. This paper provides a review of the performancerequirements, complications, and limitations of stent materials in the treatment of common digestivetract diseases. The advantages and disadvantages of different materials and processing technologiesfor digestive tract stents are discussed. Furthermore, considering the diverse requirements for idealalimentary canal stent materials, the challenges that require further research are outlined in detail,providing strategic references for the development of biomedical stents for the digestive tract.